Tinjauan Pengawasan Waktu Pelaksanaan Pada Proyek Pembangunan Dinding Penahan Tanah Kejaksaan Tinggi Sumatera Selatan - Dicky, Achmad; Ely Mulyati (Yayasan Literasi Sains Indonesia, 2025)
This study aims to evaluate the suitability between planning and realization of implementation time in the retaining wall construction project at the South Sumatra High Prosecutor's Office. Using quantitative descriptive method and case study approach, data was obtained through direct observation, documentation, and analysis of weekly and monthly project reports. The S-curve is used as the main tool in monitoring the deviation between the planned and realized work weights. The results showed that in general the project was on schedule, although there was a negative deviation in weeks 7 to 9 due to weather constraints, material delays, and labor shortages. However, through acceleration strategies such as overtime and improved logistics management, delays were minimized. Structured time monitoring proved effective in keeping the project within schedule tolerance limits. This research emphasizes the importance of an adaptive monitoring system as well as good coordination between teams as keys to successful implementation of construction projects.